Outcome of chronic granulomatous disease ‐ Conventional treatment vs stem cell transplantation. Issue 3 (22nd November 2020) - Dedieu, Cinzia; Albert, Michael H.; Mahlaoui, Nizar; Hauck, Fabian; Hedrich, Christian; Baumann, Ulrich; Warnatz, Klaus; Roesler, Joachim; Speckmann, Carsten; Schulte, Johannes; Fischer, Alain; Blanche, Stephane; et al.
Abstract: Background: Hematopoietic stem cell transplantation (HSCT) can cure chronic granulomatous disease (CGD), but it remains debated whether all conventionally treated CGD patients benefit from HSCT. Methods: We retrospectively analyzed 104 conventionally treated CGD patients, of whom 50 patients underwent HSCT. Results: On conventional treatment, seven patients (13%) died after a median time of 16.2 years (interquartile range [IQR] 7.0‐18.0). Survival without severe complications was 10 ± 3% (mean ± SD) at the age of 20 years; 85% of patients developed at least one infection, 76% one non‐infectious inflammation. After HSCT, 44 patients (88%) were alive at a median follow‐up of 2.3 years (IQR 0.8‐4.9): Six patients (12%) died from infections. Survival after HSCT was significantly better for patients transplanted ≤8 years (96 ± 4%) or for patients without active complications at HSCT (100%). Eight patients suffered from graft failure (16%); six (12%) developed acute graft‐vs‐host disease requiring systemic treatment. Conventionally treated patients developed events that required medical attention at a median frequency of 1.7 (IQR 0.8‐3.2) events per year vs 0 (IQR 0.0‐0.5) in patients beyond the first year post‐HSCT. While most conventionally treated CGD patients failed to thrive, catch‐up growth after HSCT in surviving patients reached the individual percentiles at the age of diagnosis of CGD. Conclusion: Chronic granulomatous disease patients undergoing HSCT until 8 years of age show excellent survival, but young children need more intense conditioning to avoid graft rejection. Risks and benefits of HSCT for adolescents and adults must still be weighed carefully. Abstract :